Manifestaciones orales en pacientes con alteraciones de las glándulas tiroides. - Paredes Gavilanes, María Sol (2023)
The main objective of this research study was to analyze the relationship between oral manifestations and thyroid gland disorders. A systematic review was carried out, considering the PRISMA methodology, a question was drafted according to the PICO technique, and the search was carried out until October 2023 in the databases: Pubmed, Embase, Scopus and Web of Science, no date or language filters were applied, the following information was extracted: author, year of publication, journal, sample size, sample age, gender, groups, methodology, signs and symptoms, diagnosis, thyroid gland alterations, oral manifestations, treatment and relationship between thyroid alterations and oral manifestations. The data search yielded 242 articles and 16 studies met the criteria, where most of the investigations are observational case reports and case-control studies. Women aged 27-59 years are the most affected by hypothyroidism (Hashimoto's thyroiditis and thyroid nodule), primary hyperparathyroidism, and ectopic thyroid and papillary carcinoma. Oral manifestations were oral lichen planus (OLP), caries, dental plaque, enamel defects, crossbite, macroglossia, oral mass formation, and burning mouth syndrome. Hypothyroidism is associated with OLP, crossbite, enamel defect, parathyroid adenoma, and severe gingivitis due to primary hyperparathyroidism, burning mouth syndrome in Hashimoto's thyroid patients, without evidence of signs and symptoms. In addition, very difficult to occur cases such as papillary carcinoma due to ectopic thyroid tissue and Pendred's syndrome with macroglossia are reported.